Influence of H-FABP gene polymorphisms on slaughter value of hybrid pigs - Nyisalovits, Andrea; Posta, János; Czeglédi, Levente; Juhász, Diána; Babinszky, László (Acta Agraria Debreceniensis, 2018)
The H-FABP gene was defined as a potential candidate gene influencing the fat deposition traits, primarily the intramuscular fat content. The aim of this study is to define whether the previously reported gene mutations are connected with the slaughter traits measured in a standard slaughterhouse. The study included data from 405 gilts and barrows from 2 different samples. The two chosen mutation (HFABP1: c. 103 T>C, HFABP2: c. 1970 T>C) were detected in one reaction with PCR-RFLP (Polymerase Chain Reaction-Restriction Fragment Lenght Polymorphism) method with HinfI restrictoin enzyme. The allel frequencies are as follows: 103T(H)=0.75; 103C(h)=0.25, 1970T=0.32; 1970C=0.68. A HFABP1 mutation has significant effect on backfat thickness and lean meat % at stable 1 (sample 1), but there were no effect at stable 2 (sample 2). The analysis of values of production traits, depending on HFABP2 genotype did not reveal significant differences. Based on this study we can’t get a clear conclusion on the impact of polymorphisms on production parameters. In the examined flock the allele frequency of mutation in 5 'UTR is identical to the literature data, i. e. the more favorable variant regarding the intramuscular fat content is predominant in the population.